If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -2x = 8x + 8 Combine like terms: 8x + -2x = 6x 6x = 8x + 8 Reorder the terms: 6x = 8 + 8x Solving 6x = 8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 6x + -8x = 8 + 8x + -8x Combine like terms: 6x + -8x = -2x -2x = 8 + 8x + -8x Combine like terms: 8x + -8x = 0 -2x = 8 + 0 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| x+4.81=12.95 | | F(x)=4x^2-12x^2-16x | | 45+30=15 | | y=(-1/4x)-2 | | -16x^2+64x+1024=y+1024 | | y=12-.5x | | 7=x(-3-6)(-3+9) | | 5x-14+26=-9 | | 2-(2x-4)=2x-9 | | 1-7m=8-6m | | x+5=4-x+3 | | 6b+7=2b-13 | | 4-5(s+2)=3+(s+1)-1 | | -9d=27 | | 2[x+(x+10)]=180 | | 6x^2=12x-20 | | x^4-1x^2+80=0 | | 4x-y-2=0 | | 9x+60=177 | | (1/7x^2y^3)(y^3z^5)(28x^3z^4) | | 2ln(4-3t)+1=7 | | 3x-4y-4=0 | | 8a+6(2a-6)=4a-4 | | 5x^4+126x^2+25=0 | | -12x/15x | | .38=0.0021x^2-0.286x+16.28 | | 6+4t-4=9t+9-6t | | -2(v+8)=-8 | | 3.2*24= | | .4*x-6=12 | | 6x/8x2 | | n-5/5=n+2/9 |